2022
DOI: 10.33590/emjgastroenterol/10102824
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Anti-TNFs in Immune-Mediated Disease

Abstract: TNF-α is produced in high concentrations in chronic inflammatory disease, resulting in excessive inflammation which eventually leads to organ damage. The advent of anti-TNF therapy in clinical practice 20 years ago represented a significant change in the management of immune-mediated inflammatory diseases (IMIDs), including rheumatoid arthritis (RA), axial spondylarthritis (SpA), psoriasis, and inflammatory bowel disease (IBD). There are five anti-TNFs approved for use in IMIDs: infliximab, adalimumab, golimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…TNF-α biologics, such as adalimumab, have been a key part of the treatment algorithms for RA and CD for several decades. 1,3 Most biologic therapies for IMIDs, including adalimumab, are delivered subcutaneously via devices such as prefilled syringes or autoinjectors, both of which allow for convenient self-administration by patients. 4,5 Previous studies have reported patient preference for autoinjectors over prefilled syringes, in terms of reduced discomfort, ease of use, and improved adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α biologics, such as adalimumab, have been a key part of the treatment algorithms for RA and CD for several decades. 1,3 Most biologic therapies for IMIDs, including adalimumab, are delivered subcutaneously via devices such as prefilled syringes or autoinjectors, both of which allow for convenient self-administration by patients. 4,5 Previous studies have reported patient preference for autoinjectors over prefilled syringes, in terms of reduced discomfort, ease of use, and improved adherence.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α biologics, such as adalimumab, have been a key part of the treatment algorithms for RA and CD for several decades. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%